2019
DOI: 10.3389/fmicb.2019.00107
|View full text |Cite
|
Sign up to set email alerts
|

Survival Mechanisms of Campylobacter hepaticus Identified by Genomic Analysis and Comparative Transcriptomic Analysis of in vivo and in vitro Derived Bacteria

Abstract: Chickens infected with Campylobacter jejuni or Campylobacter coli are largely asymptomatic, however, infection with the closely related species, Campylobacter hepaticus, can result in Spotty Liver Disease (SLD). C. hepaticus has been detected in the liver, bile, small intestine and caecum of SLD affected chickens. The survival and colonization mechanisms that C. hepaticus uses to colonize chickens remain unknown. In this study, we compared the genome sequences of 14 newly sequenced Australian isolates of C. he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 68 publications
3
32
1
Order By: Relevance
“…Two isolates contained plasmids with very high sequence similarity to C. jejuni pTet-like plasmids. C. hepaticus isolates from Australia and UK have previously been reported to contain tetracycline-resistant plasmids, but they contained different C. jejuni and C. coli plasmids (11,12). Currently, chlortetracycline is the main treatment option available for the control of SLD in Australia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two isolates contained plasmids with very high sequence similarity to C. jejuni pTet-like plasmids. C. hepaticus isolates from Australia and UK have previously been reported to contain tetracycline-resistant plasmids, but they contained different C. jejuni and C. coli plasmids (11,12). Currently, chlortetracycline is the main treatment option available for the control of SLD in Australia.…”
Section: Discussionmentioning
confidence: 99%
“…Campylobacter hepaticus ranges in size from 0.3 to 0.4 µm wide and 1.0-1.2 µm long (3,8,9). Campylobacter hepaticus has a reduced genome size (1.48-1.51 Mb) and a lower G+C content (27.9-28.5%) than most Campylobacter species (11,12). Campylobacter hepaticus grows slowly in vitro; requiring at least 3 days for visible colonies to form on blood agar (3,8).…”
Section: Introductionmentioning
confidence: 99%
“…In a detailed analysis of the genome of Australian and UK isolates of C. hepaticus , Van et al () showed that clonal populations of C. hepaticus were geographically confined. They also demonstrated that there was divergence from the other Campylobacter infecting poultry ( C. jejuni and C. coli ) indicating that there were barriers to gene transfer between these species.…”
Section: Genomic Analysis Of C Hepaticusmentioning
confidence: 99%
“…In another challenge, the C. hepaticus 44L strain was used and the assay successfully detected antibodies induced by this strain (data not shown). It has been reported that the genomes of C. hepaticus strains are highly similar (Van et al 2019), therefore the expectation is that the immunoassay could reliably test antibody responses produced by other C. hepaticus strains.…”
Section: Discussionmentioning
confidence: 99%
“…The cross reactivity of C. hepaticus antigens with antibodies to other common campylobacters was anticipated to be one of the major challenges in developing a species-specific assay. Nearly 70% of the genes in C. hepaticus are conserved in C. jejuni and C. coli strains (Van et al, 2019). It is not uncommon to find C. jejuni and C. coli in flocks since most chickens get exposed to them early in their life and a majority harbour them as commensal bacteria in the intestine and caecum (Lindblom et al, 1986;Van et al, 2018).…”
Section: Introductionmentioning
confidence: 99%